Design web-based Aplikasi Sistem Informasi Keuangan (ASIK) at Perwakilan BPKP Provinsi Riau - Ziddo Simanjuntak; Zulfahmi Syahputra; Arpan (Sean Institute, 2021)
In Perwakilan BPKP Provinsi Riau, before official work travel, the officer needs to prepare some documents such as Assignment Letter and Cost Sheet, while the Administrator should make Official Work Travel Letter and Treasurer Accountability Report. To make all the documents the officer has to use other work unit application, and it needs some prodecures to be done that makes the process ineffective and inefficient. Other than that there is no application to monitor the budget yet. So we create a web based application that called Aplikasi Sistem Informasi Keuangan (ASIK) which use waterfall method. Result of the research is documents that needed in official travel can be made faster with ASIK so performance of every officer can be more effective and efficient. Also, with ASIK, leader and administrator can monitor the budget easily.